Initial validation of ozone measurements from the High Resolution Dynamics Limb Sounder - Nardi, Bruno (2008)
Comparisons of the latest High Resolution Dynamics Limb Sounder (HIRDLS) ozone retrievals (v2.04.09) are made with ozonesondes, ground-based lidars, airborne lidar measurements made during the Intercontinental Chemical Transport Experiment–B, and satellite observations. A large visual obstruction blocking over 80% of the HIRDLS field of view presents significant challenges to the data analysis methods and implementation, to the extent that the radiative properties of the obstruction must be accurately characterized in order to adequately correct measured radiances. The radiance correction algorithms updated as of August 2007 are used in the HIRDLS v2.04.09 data presented here. Comparisons indicate that HIRDLS ozone is recoverable between 1 and 100 hPa at middle and high latitudes and between 1 and 50 hPa at low latitudes. Accuracy of better than 10% is indicated between 1 and 30 hPa (HIRDLS generally low) by the majority of the comparisons with coincident measurements, and 5% is indicated between 2 and 10 hPa when compared with some lidars. Between 50 and 100 hPa, at middle and high latitudes, accuracy is 10–20%. The ozone precision is estimated to be generally 5–10% between 1 and 50 hPa. Comparisons with ozonesondes and lidars give strong indication that HIRDLS is capable of resolving fine vertical ozone features (1–2 km) in the region between 1 and 50 hPa. Development is continuing on the radiance correction and the cloud detection and filtering algorithms, and it is hoped that it will be possible to achieve a further reduction in the systematic bias and an increase in the measurement range downward to lower heights (at pressures greater than 50–100 hPa).